Structure, microstructure, ferroelectric/electromechanical properties and retention characteristics of [Bi1-x Nb (x) ]FeO3 thin films - Simões, Alexandre Zirpoli [UNESP]; Cavalcante, L. S. [UNESP]; Moura, F.; Batista, N. C.; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Springer, 2012)
In this work, we report the structure, microstructure, ferroelectric/electromechanical properties, and retention characteristics of [Bi1-x Nb (x) ]FeO3 (BNFO) thin films [x=0,0.025,0.05, and 0.1] prepared by the polymeric precursor method. X-ray patterns analyses and Rietveld refinement data confirmed that BNFO thin films have a rhombohedral structure and can be obtained at 773 K for 2 h in static air. However, a small quantity of deleterious phase related to Bi2Fe4O9 was observed with the addition of niobium (Nb). Structural refinement data indicated that the substitution of bismuth (Bi) by Nb in the A-site leads to a reduction in lattice parameters and the unit cell volume. Supercell models representing the [BiO6],[NbO6], and [FeO6] clusters which are present in the rhombohedral lattice are shown here. Atomic force microscopy images showed a reduction in the average grain size of films with the substitution of Bi by Nb. Ferroelectric and electromechanical properties were confirmed by hysteresis loops and piezoresponse force microscopy. Ferroelectric/electromechanical properties and retention characteristics indicated that the BNFO films with x=0.1 have a large remnant polarization, a low coercive field, a piezoelectric coefficient (d (33)a parts per thousand 38 pm/V), and good retention resistance.